2000
DOI: 10.3171/jns.2000.93.6.0958
|View full text |Cite
|
Sign up to set email alerts
|

Primary intracerebral and aneurysmal subarachnoid hemorrhage in Izumo City, Japan. Part 1: incidence and seasonal and diurnal variations

Abstract: The actual incidence rates of both primary ICH and aneurysmal SAH seem to be much higher than have been reported so far. In addition, the data indicate the existence of seasonal periodicity for men and younger patients with ICH, and that the risk of both ICH and SAH is lower during nighttime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 74 publications
5
74
0
3
Order By: Relevance
“…This is in concordance with other studies available in literature with most of their patients in the 5 th & 6 th decade of life [12,16,19]. In Inagawa et al [20], [21] series more patients were in age range of 17-93 years. Maximum number of patients was in the 7 th decades of life.…”
Section: Discussionsupporting
confidence: 81%
“…This is in concordance with other studies available in literature with most of their patients in the 5 th & 6 th decade of life [12,16,19]. In Inagawa et al [20], [21] series more patients were in age range of 17-93 years. Maximum number of patients was in the 7 th decades of life.…”
Section: Discussionsupporting
confidence: 81%
“…Climate changes such as daily temperature, humidity, and atmospheric pressure have been proposed to influence seasonal patterns of SAH occurrence in previous studies. 4,12,14) The following meteorological factors were associated with the occurrence of SAH: Falling atmospheric pressure and/or dropping dew point temperature, 4) changes in atmospheric pressure, 15) and association with short length of sunshine, low minimal humidity, and low maximum temperature on the day of SAH, and low maximal temperature and low atmospheric pressure on the day before SAH. 20) The present study found that DT(max -min) was the highest in spring when the incidences of SAH in men and women were the highest and second highest, respectively, and mean H was the highest in Meteorological Factors and Sex in Patients With SAH in Japan winter when the incidence of SAH in women was the highest.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6]15,20,24,26,32,33) No statistically significant seasonal variations were also observed in some studies. 2,12,14,17,22,27,[29][30][31] The highest occurrences of SAH were found in spring in women and in late fall in men, 4) in spring and fall in men, and in winter in women, 24) and in winter in women and no peak in men. 32) Our data resembled the results of 10 years of the Canadian Collaborative Study Group although the lowest occurrence in their male group was in summer whereas that of in the present study was in winter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations